Peningkatan Kemampuan Berpikir Kritis Dengan Penerapan Model Kooperatif Tipe TGT Dengan Quick And Smart Berbantuan Aplikasi Quizizz - Iman Mahardika; Astri Srigustini; Gugum Gumilar (CV. Ulil Albab Corp, 2024)
This research is motivated by the problems that occur at SMAN 1 Sindangkasih, namely the low critical thinking skills of students. The purpose of this study was to determine the effect of the application of the teams games tournament type cooperative learning model with quick and smart assisted by the quizizz application in improving students' critical thinking skills in economic subjects. The method used is an experimental method with a type of quasi experiment, the research design uses a non-equivalent control group design, and the data collection technique is through a description test. The population in this study were all XI social studies classes at SMAN 1 Sindangkasih in the 2023/2024 school year totalling 143 students. The sample used was class XI IPS 4 which numbered 36 students as an experimental class and class XI IPS 3 as a control class with sampling using purposive sampling technique. Based on the results of the study, it shows that there is an effect of the team games tournament type cooperative learning model with quick and smart assisted by the quizizz application on students' critical thinking skills in the experimental class, where Ha is accepted if the sig. (2-tailed) value ≤0.05 and based on research obtained a sig. (2-tailed) value of 0.000 <0.05. The average value of the experimental class is higher than the control class, it can be concluded in this study that the learning model used in the experimental class can improve students' critical thinking skills.